Pendampingan Pengembangan Soft Skills Bagi Mahasiswa Baru Kesehatan Masyarakat Universitas Sriwijaya - Muhammad Naufan Rizqullah; Muhammad Ridwan Afandi; Jafar Arifin; Dyah Ambarwati; M.Buana Firzatulloh (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
The development of soft skills has become an important aspect in preparing students to face the challenges of education and the professional world, especially in an era full of uncertainty and dynamic changes (VUCA). Community service aims to assist new students of the Public Health Study Program at Sriwijaya University, Class of 2024, in recognizing their potential, building leadership character, and planning their life during their study period. The method used is Participatory Action Research (PAR) with stages including identifying student potential through questionnaires, collaborative planning with the student organization (Himkesma), offline soft skill training, and continued consultation guidance. The results of the activities showed an increase in students’ understanding of the importance of soft skills, interest in active organizational participation, and readiness to develop their potential through various campus experiences. Evaluation and reflection confirmed that soft skill development assistance strengthened the students’ human resource capacity and encouraged new students to actively participate in organizations as a means of developing leadership and interpersonal skills.This activity significantly contributes to equipping students to be better prepared to face competition in the workforce and the challenges of future life.